The photosensitizer-based therapies enhance the repairing of skin wounds - Ning, Xiaoying; He, Gang; Zeng, Weihui; Xia, Yumin (Frontiers in Medicine, 2022)
Wound repair remains a clinical challenge and bacterial infection is a common complication that may significantly delay healing. Therefore, proper and effective wound management is essential. The photosensitizer-based therapies mainly stimulate the photosensitizer to generate reactive oxygen species through appropriate excitation source irradiation, thereby killing pathogenic microorganisms. Moreover, they initiate local immune responses by inducing the recruitment of immune cells as well as the production of proinflammatory cytokines. In addition, these therapies can stimulate the proliferation, migration and differentiation of skin resident cells, and improve the deposition of extracellular matrix; subsequently, they promote the re-epithelialization, angiogenesis, and tissue remodeling. Studies in multiple animal models and human skin wounds have proved that the superior sterilization property and biological effects of photosensitizer-based therapies during different stages of wound repair. In this review, we summarize the recent advances in photosensitizer-based therapies for enhancing tissue regeneration, and suggest more effective therapeutics for patients with skin wounds.